Chirality in Modern Antidepressants: A Comprehensive Review of Stereochemical Impacts on Pharmacology and Therapeutics - Gabriel Hancu; Alexandra Uilăcan; Nicoleta Mirela Blebea (Drugs and Drug Candidates)
The review explores the critical role of chirality in the pharmacology of antidepressant drugs, focusing on how the stereochemistry of these compounds influences their biological activity and therapeutic outcomes. Antidepressants, especially modern classes such as selective serotonin reuptake inhibitors (SSRIs) and serotonin–norepinephrine reuptake inhibitors (SNRIs), often possess chiral centers that result in enantiomers with distinct pharmacodynamic and pharmacokinetic profiles. The review systematically examines various chiral antidepressants, including racemic mixtures and enantiomerically pure drugs, highlighting the differential effects of each enantiomer on neurotransmitter reuptake inhibition and the potential clinical implications. By examining specific examples of chiral antidepressants, the review illustrates the differences in pharmacokinetics and pharmacodynamics between enantiomers and racemic mixtures, emphasizing the clinical advantages of using enantiomerically pure compounds. Understanding and leveraging chirality in drug design and therapy is crucial for optimizing antidepressant treatments, offering insights into future research directions that could enhance patient outcomes by tailoring medication more precisely to individual biological profiles.